A low-precipitation environmentally friendly WPC wood plastic floor lubricating material and preparation method thereof

By using the lubricant of a specific component in PVC basewood plastic composite plates, the high compatibility and flame retardant performance of the wood component and polyvinyl chloride are realized, and the existing plate materials are poor in light and thermal stability and poor compatibility. The problem improves the overall performance and environmental protection of the board.

CN118931087BActive Publication Date: 2025-01-24CHANGZHOU KESAI SUCCESS PLASTICS MATERIALS CO LTD

Patent Information

Application Number
CN202411418600.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-24
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

The existing PVC-based wood-plastic composite boards have poor light and thermal stability, and the compatibility of wood raw materials with PVC is poor, resulting in performance defects and precipitation problems.

Method used

The lubricants of methacryal methacrylate polypropylene wax, MBS resin powder, chlorine chloride, TPP phosphate and zinc borate are used to improve the compatibility of wooden ingredients and polyvinyl chloride compatibility through cross -linking reactions , And improve the flow of flow and flame retardant through complexity and fillers.

Benefits of technology

Effectively improved the compatibility, mechanical properties, chemical stability and flame retardant performance of PVC base wood plastic composite plates, avoiding component analysis, and improving the overall performance and environmental protection of the board.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application discloses a low-precipitation environmentally friendly WPC wood-plastic floor lubricating material and a preparation method thereof. On the one hand, the present application provides a low-precipitation environmentally friendly WPC wood-plastic floor lubricating material, and the mass proportion of each raw material component of the lubricant includes: 20 to 28 parts of methyl methacrylate grafted polypropylene wax, 32 to 40 parts of MBS resin powder, 8 to 16 parts of chlorinated paraffin, 16 to 22 parts of TPP tritolyl phosphate, 4 to 10 parts of zinc borate, and 2 to 8 parts of silicone powder. On the other hand, the present application provides a preparation method for the above-mentioned low-precipitation environmentally friendly WPC wood-plastic floor lubricating material. The present application effectively improves the compatibility between wood components and polyvinyl chloride without any precipitation, and can comprehensively improve the various properties and flame retardant properties of PVC-based wood-plastic composite panels.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of wood plastic lubricants, and in particular to a low-precipitation environmentally friendly WPC wood plastic floor lubricating material and a preparation method thereof. Background Art

[0002] Wood Plastic Composites (WPC) is a new type of environmentally friendly high-tech material that can replace wood and plastic. Wood Plastic Composites is mainly based on wood (wood cellulose, plant cellulose) and thermoplastic polymer materials (plastics). After adding various processing aids and mixing them evenly, they are heated and extruded by mold equipment to form a high-tech green environmentally friendly material. It has the performance and characteristics of both wood and plastic.

[0003] PVC-based wood-plastic composite board is one of the most widely used wood-plastic floor boards at present. It combines the advantages of wood and PVC plastic and has relatively excellent performance. PVC-based wood-plastic composite board has high dimensional stability, natural wood texture, no wood knots, low water absorption, good anti-mildew and anti-termite performance, and excellent secondary processing performance. In addition, PVC-based wood-plastic composite board is green and environmentally friendly, and can realize the recycling and reuse of waste plant fibers and plastics, and the board itself can also be recycled and reused.

[0004] Existing PVC-based wood-plastic composite boards require the addition of various additives due to the poor stability of PVC to light and heat and its easy aging. In addition, the compatibility between PVC and wood raw materials is very poor, and lubricants need to be added to overcome the compatibility problem. Most of the lubricants currently used are alkaline stearates, low-melting polymers, low-boiling oils and / or maleic anhydride grafted polymers. Alkaline stearates are easy to destroy the acidic additives in the board, and are also easy to react with acidic maleic anhydride grafted polymers, resulting in limited improvement in compatibility, which in turn leads to defects in board performance; low-melting polymers and low-boiling oils are easy to precipitate from the board, and are prone to loss during the hot melt processing. There will also be quality and environmental problems due to precipitation in daily use. Summary of the invention

[0005] In order to solve at least one of the above technical problems, a lubricant is developed that effectively improves the compatibility between wood components and polyvinyl chloride, has no precipitation, and can comprehensively improve the various properties and flame retardant properties of PVC-based wood-plastic composite boards. The present application provides a low-precipitation environmentally friendly WPC wood-plastic floor lubricating material and a preparation method thereof.

[0006] On the one hand, the present application provides a low-precipitation environmentally friendly WPC wood-plastic floor lubricating material, wherein the mass proportion of the raw material components of the lubricant includes: 20 to 28 parts of methyl methacrylate grafted polypropylene wax, 32 to 40 parts of MBS resin powder, 8 to 16 parts of chlorinated paraffin, 16 to 22 parts of TPP tricresyl phosphate, 4 to 10 parts of zinc borate, and 2 to 8 parts of silicone powder.

[0007] Optionally, the mass proportions of the raw material components of the lubricant include: 22-24 parts of methyl methacrylate grafted polypropylene wax, 36-38 parts of MBS resin powder, 10-12 parts of chlorinated paraffin, 18-20 parts of TPP tricresyl phosphate, 6-8 parts of zinc borate, and 4-6 parts of silicone powder.

[0008] Optionally, the grafting rate of the methyl methacrylate grafted polypropylene wax is 5-10%.

[0009] Optionally, the method for preparing the methyl methacrylate grafted polypropylene wax comprises the following steps:

[0010] S1-1, dissolving benzophenone in ethanol to prepare an initiator solution;

[0011] S1-2. In a light-proof condition, add methyl methacrylate to the initiator solution of step S1-1 to prepare a reaction solution;

[0012] S1-3. In a light-proof condition, add polypropylene wax powder to the reaction solution prepared in step S1-2, and disperse by ultrasonication to prepare a reaction dispersion;

[0013] S1-4. The reaction dispersion prepared in step S1-3 is subjected to ultraviolet irradiation for more than 10 minutes under nitrogen protection, and the solid reaction product is filtered out, washed, and dried to obtain methyl methacrylate grafted polypropylene wax.

[0014] Further optionally, in step S1-1, the concentration of benzophenone in the initiator solution is 40-60 g / L.

[0015] Further optionally, in step S1-2 and step S1-3, the mass ratio of the added amount of methyl methacrylate and polypropylene wax powder is 0.7~1.4:10.

[0016] Optionally, in step S1-4, the power of the ultraviolet light source for ultraviolet irradiation is not less than 1000W.

[0017] Optionally, the particle size of the zinc borate is 100-325 mesh.

[0018] On the other hand, the present application provides a method for preparing the above-mentioned low-precipitation environmentally friendly WPC wood plastic floor lubricating material, comprising the following steps:

[0019] S1, preparing methyl methacrylate grafted polypropylene wax;

[0020] S2, accurately weighing the formula amount of methyl methacrylate grafted polypropylene wax, chlorinated paraffin, tricresyl phosphate and zinc borate, and mixing them thoroughly to obtain a mixture a;

[0021] S3, accurately weigh the MBS resin powder and silicone powder in the formula, mix them thoroughly, and obtain a mixture b;

[0022] S4, adding the mixture a obtained in step S2 and the mixture b obtained in step S3 into a twin-screw extruder, and obtaining a low-precipitation environmentally friendly WPC wood-plastic floor lubricating material through extrusion and granulation.

[0023] Optionally, in step S4, the temperature of each section of the twin-screw extruder is controlled within 165°C.

[0024] In summary, the present invention includes at least one of the following beneficial technical effects:

[0025] 1. This application uses methyl methacrylate grafted polypropylene wax as the main component of the lubricant. The polar methyl methacrylate groups contained in the above components are cross-linked with the hydrophilic groups contained in the wood powder, so that the wood powder and polyethylene or polypropylene are cross-linked, which greatly improves its lipophilicity and thus improves the compatibility of the wood powder with PVC. In addition, methyl methacrylate grafted polypropylene wax has a relatively high melting point and a basically neutral pH value. It is not easy to precipitate after addition and will not cause too much impact on the acidic or alkaline additives in the PVC sheet.

[0026] 2. The present application uses chlorinated paraffin and TPP tritolyl phosphate as another main component of the lubricant, which can effectively improve the rheological properties of the wood powder and PVC mixture and further improve the compatibility between the two; in addition, the boiling point of the above components is relatively high. After adding a small amount of silicone powder in the present application, it can ensure that the above lubricant components will not precipitate.

[0027] 3. The present application contains MBS resin powder, which can effectively improve the mechanical properties of PVC and the chemical stability of PVC while improving the compatibility of PVC with wood powder.

[0028] 4. This application is compounded with chlorinated paraffin and TPP tritolyl phosphate, and zinc borate is added as a filler. In addition to ensuring that the lubricant does not precipitate and effectively improving the compatibility of PVC and wood powder, it can also effectively improve the flame retardant properties of PVC-based wood-plastic composite panels and significantly reduce the amount of smoke generated during combustion. DETAILED DESCRIPTION

[0029] The present application is further described in detail below in conjunction with embodiments.

[0030] The present application designs a low-precipitation environmentally friendly WPC wood-plastic floor lubricating material, wherein the mass proportion of each raw material component of the lubricant includes: 20-28 parts of methyl methacrylate grafted polypropylene wax, 32-40 parts of MBS resin powder, 8-16 parts of chlorinated paraffin, 16-22 parts of TPP tricresyl phosphate, 4-10 parts of zinc borate, and 2-8 parts of silicone powder.

[0031] Prior to this application, lubricants for PVC wood-plastic composite materials in the art generally use alkaline stearates compounded with wax components such as paraffin wax and PE wax, and some lubricants also add amide components, maleic anhydride grafted polymers and / or oil components, etc. This type of lubricant will have the various problems mentioned in the background technology.

[0032] In addition, in the prior art, most PVC-based wood-plastic composite boards are used as the material of wood-plastic flooring, and flame retardancy is a major consideration. PVC materials have good flame retardant properties, and their use in the field of building materials can effectively solve the problem of building fire prevention. However, PVC materials also have a big problem. Since they contain more chlorine elements, they will produce a large amount of toxic smoke when they encounter fire. To solve the problem of large amounts of combustion smoke, it is necessary to add various flame retardant additives to achieve a smoke suppression effect. The addition of these flame retardant additives will, on the one hand, make the composition of PVC-based wood-plastic composite boards more complex, thereby affecting the various properties of the boards and also affecting their processing performance; on the other hand, the complex composition will cause some components in the lubricant to react with the additives, thereby resulting in a decrease in the lubrication effect and flame retardant effect.

[0033] The present application is designed based on the above-mentioned existing technical problems after comprehensive consideration. The present application adopts methyl methacrylate grafted polypropylene wax as the main component of the lubricant, which can not only improve the compatibility of the various components of the PVC-based wood-plastic composite board, but also react with wood powder to form a cross-linked structure, effectively locking the various components of the board and preventing the components from being separated out.

[0034] In addition, the formula design of the lubricating agent of the present application takes into account aspects such as flame retardancy, smoke suppression and compatibility. The lubricating agent of the present application is mainly composed of chlorinated paraffin and TPP tricresyl phosphate, and zinc borate is added as a filler. Tricresyl phosphate can achieve a good lubricating effect and is also a halogen-free flame retardant. In the design of the present application, the introduction of this component can not only improve the flame retardant effect, but also effectively suppress the generation of toxic fumes. Chlorinated paraffin is a good lubricant for PVC materials and is also a non-toxic flame retardant. After adding zinc borate filler, it can also effectively reduce the amount of smoke generated during combustion. Such a ratio design, used in PVC-based wood-plastic composite panels, can greatly reduce the amount of smoke generated during combustion, and the flame retardant performance is also very excellent.

[0035] The present application also adds MBS resin powder to the lubricant component to optimize the compatibility and modify the performance of the PVC material. The addition of MBS resin can greatly improve the mechanical properties of the PVC-based wood-plastic composite board, and can effectively solve the problem of precipitation of lubricants and additives. In addition, MBS resin has excellent compatibility with PVC materials and wood powder, and can improve the compatibility of various components of the PVC-based wood-plastic composite board to a certain extent.

[0036] The preparation method of the low-precipitation environmentally friendly WPC wood plastic floor lubricating material of the present application comprises the following steps:

[0037] S1, preparing methyl methacrylate grafted polypropylene wax;

[0038] S2, accurately weighing the formula amount of methyl methacrylate grafted polypropylene wax, chlorinated paraffin, tricresyl phosphate and zinc borate, and mixing them thoroughly to obtain a mixture a;

[0039] S3, accurately weigh the MBS resin powder and silicone powder in the formula, mix them thoroughly, and obtain a mixture b;

[0040] S4, adding the mixture a obtained in step S2 and the mixture b obtained in step S3 into a twin-screw extruder, and obtaining a low-precipitation environmentally friendly WPC wood-plastic floor lubricating material through extrusion and granulation.

[0041] The preparation method of the present application adopts the process of mixing, extruding and granulating to prepare the lubricating material of the present application. In addition to uniformly mixing the components, it also solves the problem that some components of the existing lubricants are easily volatilized and lost during storage. In addition, after being prepared into granular materials, they can be directly mixed with PVC materials when preparing PVC-based wood-plastic composite boards. In the process of hot-melt preparation of boards, the lubricating material can be fully integrated with the PVC material, thereby effectively improving the lubrication effect.

[0042] The low-precipitation environmentally friendly WPC wood-plastic floor lubricating material of the present application is used to prepare a PVC-based wood-plastic composite board. The specific mass proportions of the components of the board include: 40-50 parts of PVC material (PVC raw material or recycled material), 40-50 parts of wood flour, 1-3 parts of PVC heat stabilizer, 1-3 parts of PVC light stabilizer, and 10-12 parts of the low-precipitation environmentally friendly WPC wood-plastic floor lubricating material of the present application.

[0043] The preparation method of the above-mentioned board comprises the following steps: fully mixing the formulated amount of PVC material, PVC heat stabilizer, PVC light stabilizer and the low-precipitation environmentally friendly WPC wood-plastic floor lubricating material of the present application to prepare a thermoplastic mixture; forming the thermoplastic mixture and wood powder by hot-melt extrusion to prepare a PVC-based wood-plastic composite board; and controlling the temperature of the hot-melt extrusion molding at 165-170°C.

[0044] By using the low-precipitation environmentally friendly WPC wood-plastic floor lubricating material of the present application to prepare PVC-based wood-plastic composite boards, there is no need to add PVC toughening agents and various modifiers in the proportion of the boards, and there is no need to add various flame retardant additives. The proportioning is simpler and the performance is better.

[0045] The following are preparation examples and embodiments of the present application:

[0046] The main sources of raw materials in the preparation examples and embodiments of the present application are as follows:

[0047] Methyl methacrylate, purity 99.5%, purchased from Shandong Chuangying Chemical Co., Ltd.; polypropylene wax, average molecular weight 7000-9000 (particle size 200 mesh), purchased from Wuhan Jiyesheng Chemical Co., Ltd.; benzophenone, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; nitrogen, 99% purity, purchased from Shenzhen Yuejia Gas Co., Ltd.; MBS resin powder, 99% purity, purchased from Guangdong Wengjiang Chemical Reagent Co., Ltd.; chlorinated paraffin, CE-70 (99% purity), purchased from Wuhan Jiyesheng Chemical Co., Ltd.; TPP tricresyl phosphate, 99% purity, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; zinc borate, 99% purity (particle size 100 mesh and 325 mesh), purchased from Shandong Zhengxing New Materials Co., Ltd.; silicone powder, purchased from Shanghai Jinghong Chemical Technology Co., Ltd.; heat stabilizer for PVC, calcium zinc stabilizer for PVC, purchased from Shanghai Xige Biotechnology Co., Ltd.; light stabilizer for PVC, light stabilizer 994, purchased from Guangzhou Shanghe Chemical Technology Co., Ltd.

[0048] The following are preparation examples 1 to 4 of this application

[0049] In Preparation Examples 1 to 4 of the present application, a vacuum ultraviolet oven is used as the irradiation equipment, and the ultraviolet light source power of the oven is 1000W.

[0050] Preparation Example 1

[0051] The preparation method of the methyl methacrylate grafted polypropylene wax of this preparation example comprises the following steps:

[0052] S1-1, dissolving benzophenone in ethanol to prepare an initiator solution with a benzophenone concentration of 40 g / L;

[0053] S1-2. Under light-shielding conditions, methyl methacrylate was added to the initiator solution of step S1-1 to prepare a reaction solution with a methyl methacrylate concentration of 140 g / L;

[0054] S1-3. Under light-proof conditions, add polypropylene wax powder to the reaction solution prepared in step S1-2 at a mass ratio of methyl methacrylate to polypropylene wax powder of 0.7:10, and ultrasonically disperse for 30 minutes to prepare a reaction dispersion;

[0055] S1-4. Place the reaction dispersion prepared in step S1-3 in a sealed UV oven under nitrogen protection, maintain the temperature at 40°C, and irradiate with UV for 10 minutes. Filter out the solid reaction product, wash it repeatedly with ethanol and deionized water, and then dry it in a vacuum drying oven at 40°C to obtain methyl methacrylate grafted polypropylene wax powder.

[0056] Preparation Example 2

[0057] The preparation method of the methyl methacrylate grafted polypropylene wax of this preparation example comprises the following steps:

[0058] S1-1, dissolving benzophenone in ethanol to prepare an initiator solution with a benzophenone concentration of 60 g / L;

[0059] S1-2. Under light-shielding conditions, methyl methacrylate was added to the initiator solution of step S1-1 to prepare a reaction solution with a methyl methacrylate concentration of 140 g / L;

[0060] S1-3. Under light-proof conditions, add polypropylene wax powder to the reaction solution prepared in step S1-2 at a mass ratio of methyl methacrylate to polypropylene wax powder of 0.7:10, and ultrasonically disperse for 30 minutes to prepare a reaction dispersion;

[0061] S1-4. Place the reaction dispersion prepared in step S1-3 in a sealed UV oven under nitrogen protection, maintain the temperature at 40°C, and irradiate with UV for 10 minutes. Filter out the solid reaction product, wash it repeatedly with ethanol and deionized water, and then dry it in a vacuum drying oven at 40°C to obtain methyl methacrylate grafted polypropylene wax powder.

[0062] Preparation Example 3

[0063] The preparation method of the methyl methacrylate grafted polypropylene wax of this preparation example comprises the following steps:

[0064] S1-1, dissolving benzophenone in ethanol to prepare an initiator solution with a benzophenone concentration of 60 g / L;

[0065] S1-2. Under light-shielding conditions, methyl methacrylate was added to the initiator solution of step S1-1 to prepare a reaction solution with a methyl methacrylate concentration of 140 g / L;

[0066] S1-3. Under light-proof conditions, add polypropylene wax powder to the reaction solution prepared in step S1-2 at a mass ratio of methyl methacrylate to polypropylene wax powder of 1.05:10, and ultrasonically disperse for 30 minutes to prepare a reaction dispersion;

[0067] S1-4. Place the reaction dispersion prepared in step S1-3 in a sealed UV oven under nitrogen protection, maintain the temperature at 40°C, and irradiate with UV for 10 minutes. Filter out the solid reaction product, wash it repeatedly with ethanol and deionized water, and then dry it in a vacuum drying oven at 40°C to obtain methyl methacrylate grafted polypropylene wax powder.

[0068] Preparation Example 4

[0069] The preparation method of the methyl methacrylate grafted polypropylene wax of this preparation example comprises the following steps:

[0070] S1-1, dissolving benzophenone in ethanol to prepare an initiator solution with a benzophenone concentration of 60 g / L;

[0071] S1-2. Under light-shielding conditions, methyl methacrylate was added to the initiator solution of step S1-1 to prepare a reaction solution with a methyl methacrylate concentration of 140 g / L;

[0072] S1-3. Under light-proof conditions, add polypropylene wax powder to the reaction solution prepared in step S1-2 at a mass ratio of methyl methacrylate to polypropylene wax powder of 1.4:10, and ultrasonically disperse for 30 minutes to prepare a reaction dispersion;

[0073] S1-4. Place the reaction dispersion prepared in step S1-3 in a sealed UV oven under nitrogen protection, maintain the temperature at 40°C, and irradiate with UV for 10 minutes. Filter out the solid reaction product, wash it repeatedly with ethanol and deionized water, and then dry it in a vacuum drying oven at 40°C to obtain methyl methacrylate grafted polypropylene wax powder.

[0074] The grafting rate of the methyl methacrylate grafted polypropylene wax powder prepared in Preparation Examples 1 to 4 was calculated according to the estimation formula: grafting rate = (weight of methyl methacrylate grafted polypropylene wax powder-weight of polypropylene wax powder) / weight of polypropylene wax powder. The results are shown in Table 1.

[0075]

[0076] The following are examples of this application

[0077] All the examples in this application were prepared by the following method, which specifically includes the following steps:

[0078] S1, selecting methyl methacrylate grafted polypropylene wax powder of a specific preparation example;

[0079] S2, accurately weighing the formulated amounts of methyl methacrylate grafted polypropylene wax powder, chlorinated paraffin, tricresyl phosphate and zinc borate, and mixing them thoroughly to obtain a mixture a;

[0080] S3, accurately weigh the MBS resin powder and silicone powder in the formula, mix them thoroughly, and obtain a mixture b;

[0081] S4, adding the mixture a obtained in step S2 and the mixture b obtained in step S3 into a twin-screw extruder, and obtaining a low-precipitation environmentally friendly WPC wood-plastic floor lubricating material through extrusion and granulation;

[0082] The parameters of the twin-screw extruder were set as follows: screw speed 320 rpm, temperature of each section: zone 1 160 °C, zone 2 164 °C, zone 3 168 °C, zone 4 170 °C, zone 5 165 °C.

[0083] The following are Examples 1 to 6 of this application

[0084] Examples 1 to 6 of the present application all use the methyl methacrylate grafted polypropylene wax powder prepared in Preparation Example 1, and zinc borate all uses powder with a particle size of 100 mesh. The composition ratios of each group of Examples 1 to 6 of the present application are shown in Table 2 below.

[0085]

[0086] The following are Examples 7 to 10 of this application

[0087] The ratios of Examples 7 to 9 of the present application are exactly the same as those of Example 6 of the present application, except that the methyl methacrylate grafted polypropylene wax powder is the methyl methacrylate grafted polypropylene wax powder prepared in Preparation Examples 2 to 4, respectively.

[0088] Example 10 of the present application is basically the same as Example 9 of the present application, except that zinc borate uses powder with a particle size of 325 mesh.

[0089] The following are Examples 11 to 20 of this application

[0090] Examples 11 to 20 of the present application are examples of using the low-precipitation environmentally friendly WPC wood-plastic floor lubricating material of the present application to prepare PVC-based wood-plastic composite boards.

[0091] The boards of Examples 11 to 20 of the present application adopt the following proportions: 50 parts of PVC raw materials, 40 parts of wood flour, 2 parts of PVC heat stabilizer, 2 parts of PVC light stabilizer, and 10 parts of the low-precipitation environmentally friendly WPC wood-plastic floor lubricating material of the present application.

[0092] The plates of Examples 11 to 20 of the present application are all prepared by the plate preparation method described above in the present application, and the temperature of hot melt extrusion molding is controlled at 170°C.

[0093] The boards of Examples 11 to 20 of the present application respectively use the low-precipitation environmentally friendly WPC wood-plastic floor lubricating materials of Examples 1 to 10 of the present application; the wood powder is poplar powder with a particle size of 80 to 100 meshes.

[0094] Comparative Example 1

[0095] This application uses Example 7 with publication number CN110628229A and invention name "A non-precipitating lubricant and preparation method thereof" as comparative example 1 of this application.

[0096] Comparative Example 2

[0097] This application uses a high-efficiency lubricant containing fatty acid complex esters, model ZG-MS, produced by Jiaxing Zhongcheng Environmental Protection Technology Co., Ltd. as comparative example 2.

[0098] Comparative Example 3

[0099] The difference between this comparative example and Example 10 is that an equal amount of maleic anhydride grafted polypropylene with a grafting rate of about 1.5% is used to replace the methyl methacrylate grafted polypropylene wax powder.

[0100] Comparative Example 4

[0101] The difference between this comparative example and Example 10 is that an equal amount of maleic anhydride grafted polypropylene with a grafting rate of about 1.5% is used to replace the methyl methacrylate grafted polypropylene wax powder and the MBS resin powder.

[0102] Comparative Example 5

[0103] The difference between this comparative example and Example 10 is that an equal amount of zinc stearate is used to replace TPP tricresyl phosphate.

[0104] Comparative Example 6

[0105] The difference between this comparative example and Example 10 is that an equal amount of light calcium carbonate is used to replace zinc borate.

[0106] Comparative Example 7

[0107] This application uses Example 1 with publication number CN110294904A and invention name as a PVC composite floor and its preparation process as comparative example 7. The technology of this example has been applied to many Shengxiang brand wood plastic floors sold on the market.

[0108] Comparative Example 8

[0109] This comparative example is a comparative example of a PVC-based wood-plastic composite board, and the specific proportions are as follows: 50 parts of modified PVC raw materials, 40 parts of wood flour, 2 parts of PVC heat stabilizer, 2 parts of PVC light stabilizer, and 10 parts of PVC lubricant.

[0110] The modified PVC raw material of this comparative example is prepared by mixing PVC raw material and CPE (chlorinated polyethylene) with a chlorine content of about 34% in a ratio of 75:10, and then mixing and granulating.

[0111] The PVC lubricant of this comparative example is different from the lubricating material of Example 10 of the present application in that no MBS resin powder is added.

[0112] The wood powder used in Comparative Examples 7 to 8 of the present application also adopts poplar wood powder with a particle size of 80 to 100 meshes.

[0113] Performance Testing

[0114] The present application uses the PVC-based wood-plastic composite boards prepared in Examples 11 to 20 as samples 1 to 10 for performance testing of the present application.

[0115] In this application, the lubricating materials of comparative examples 1 to 6 are used as lubricants, and the PVC-based wood-plastic composite boards prepared according to the proportions and preparation methods of the PVC-based wood-plastic composite boards of Examples 11 to 20 of this application are used as comparative samples 1 to 6 for performance testing of this application.

[0116] The present application uses the PVC-based wood-plastic composite board prepared in Comparative Examples 7-8 as comparative samples 7-8 for the performance test of the present application.

[0117] The performance tests of the present application respectively tested the apparent quality and precipitation conditions, comprehensive physical properties, flame retardant properties and aging resistance of samples 1 to 10 and comparison samples 1 to 8.

[0118] 1) Appearance quality and precipitation

[0119] According to the method described in GB∕T 24508-2020, the appearance quality, boiling water resistance and total TVOC release rate of the board were tested. The test results are shown in Table 3 below.

[0120]

[0121] It can be seen from the data in Table 3 that the appearance quality of the board samples prepared by using the lubricating materials of Examples 1 to 10 of the present application and according to the proportion and preparation method of the PVC-based wood-plastic composite board of the present application fully meets the requirements of the national standards, and the boiling water resistance is also good. After the boiling water treatment, no additives are precipitated, and the board does not release any volatile organic compounds. The appearance quality of the boards prepared by using the lubricating materials of Comparative Examples 1 to 6 and the boards of Comparative Examples 7 to 8 also fully meets the requirements of the national standards; however, the boards prepared by using the lubricating materials of Comparative Examples 1 to 4 and the boards of Comparative Examples 7 to 8 all release volatile organic compounds; the boards prepared by using the lubricating materials of Comparative Examples 2 and 5 and the boards of Comparative Example 8 all have the problem of additive precipitation; the board of Comparative Example 7 has the problem of cracking after boiling water treatment; only the comparative sample of Comparative Example 6 has basically the same performance as the samples of the embodiments of the present application.

[0122] It can be seen that the lubricating material of the present application is applied to the preparation of PVC-based wood-plastic composite boards, and the prepared boards have excellent appearance quality and no precipitation; combined with the ratio and preparation method of the PVC-based wood-plastic composite boards of the present application, the prepared boards have excellent boiling water resistance and no volatile organic compound release; and are significantly superior to the lubricating materials used in existing PVC-based wood-plastic composite boards.

[0123] 2) Comprehensive physical properties

[0124] According to the method described in GB / T 24508-2020, the static bending strength, elastic modulus, water absorption rate and fungal corrosion weight loss rate of the plate were tested; according to the method described in GB / T 13520-1992, the impact strength of the plate was tested. The test results are shown in Table 4 below.

[0125]

[0126] It can be seen from the data in Table 4 that the physical properties of the boards of samples 1 to 10 of the present application are better than those of the boards of comparative samples 1 to 8. It can be seen that the use of the lubricating material of the present application can effectively improve the compatibility between the PVC material, various additives and wood powder, thereby effectively improving the physical properties of the board; in addition, using the lubricating material of the present application, the methyl methacrylate grafted polypropylene wax powder can be cross-linked with the wood powder, and the MBS resin powder and chlorinated paraffin can better modify the PVC, thereby effectively improving the water resistance and fungal corrosion resistance of the board.

[0127] It can also be seen from the data in Table 4 that the lubricating effect of methyl methacrylate grafted polypropylene wax is much higher than that of the existing maleic anhydride grafted polymer, and the higher the grafting rate of methyl methacrylate grafted polypropylene wax, the better the improvement effect on the physical properties of the board. In addition, by optimizing the ratio of the lubricant and the particle size of the zinc borate filler in the lubricant, the physical properties of the board can be further improved.

[0128] By comparing the data of sample 10 and comparative sample 8 in Table 4, it can be seen that the use of MBS resin powder in this application has a much better effect on improving the waterproof performance and toughness of the board than CPE as a toughening agent.

[0129] 3) Flame retardant properties

[0130] The oxygen index of the board was tested according to the method of GB / T2406; the combustion smoke density of the board was tested according to the method of GB / T 8323. The size of all tested board samples was 75×75×20mm. The test results are shown in Table 5 below.

[0131]

[0132] From the data in Table 5, it can be seen that the limiting oxygen index of the plates of samples 1 to 10 of the present application exceeds 30%, and the flame retardant performance is very excellent; the limiting oxygen index of the plates of comparative samples 1 to 8 also exceeds 28%, and also has relatively excellent flame retardant performance. In addition, the combustion smoke density of the plates of samples 1 to 10 of the present application is reduced by more than 70% compared with the plates of comparative samples 1 and comparative samples 5 to 8. It can be seen that the lubricating material of the present application, using a specific lubricating component ratio with flame retardant properties, can greatly reduce the combustion smoke density.

[0133] 4) Aging resistance

[0134] According to the method described in GB∕T 24508-2020, the plates of samples 1 to 10 and comparison samples 1 to 8 were aged, and then the physical properties of the aged plates were tested according to the method described in GB∕T 24508-2020 and the method described in GB / T 13520-1992. The static bending strength, elastic modulus, water absorption and impact strength of the aged plates were mainly tested. The test results are shown in Table 6 below.

[0135]

[0136] It can be seen from the data in Table 6 that after aging treatment, the physical properties of the plates of samples 1 to 10 of the present application have not decreased significantly, and the aging resistance is also very excellent; while for the plates of comparison samples 1 to 8, after aging treatment, the physical properties have slightly decreased, and the aging resistance is slightly worse than that of samples 1 to 10 of the present application.

[0137] It can be seen that the lubricating material of the present application, by adopting a specific lubricating component ratio, can effectively improve the aging resistance of the PVC-based wood-plastic composite board.

[0138] Based on the above performance test results, the lubricating material of the present application is used for PVC-based wood-plastic composite board. With the board ratio and preparation method of the present application, the physical properties of the prepared PVC-based wood-plastic composite board are significantly improved compared with the existing PVC-based wood-plastic composite board, and the waterproof performance and aging resistance are also significantly improved, and the flame retardant performance is also significantly improved. It can be seen that the lubricating material of the present application, when used for PVC-based wood-plastic composite board, can greatly improve the physical properties, waterproof performance and aging resistance of the board in addition to no precipitation; in addition, it can also effectively improve the flame retardancy of the board, and the amount of smoke generated by combustion can also be greatly reduced.

[0139] The applicant has conducted experimental research on the board formula of the present application. Using the board ratio of the present application, within the ratio range and in accordance with the board preparation method of the present application, the quality of the prepared boards meets the requirements of the current national standards, and the various performances of the boards are not much different, and the waterproof performance, aging resistance and flame retardant properties are all excellent.

[0140] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A low precipitation environmentally friendly WPC wood plastic floor lubricating material, characterized in that: The mass proportions of the raw material components of the lubricating material include: 20-28 parts of methyl methacrylate grafted polypropylene wax, 32-40 parts of MBS resin powder, 8-16 parts of chlorinated paraffin, 16-22 parts of tricresyl phosphate, 4-10 parts of zinc borate, and 2-8 parts of silicone powder; the grafting rate of the methyl methacrylate grafted polypropylene wax is 5-10%; The preparation method of the methyl methacrylate grafted polypropylene wax comprises the following steps: S1-1, dissolving benzophenone in ethanol to prepare an initiator solution; S1-2. In a light-proof condition, add methyl methacrylate to the initiator solution of step S1-1 to prepare a reaction solution; S1-3. In a light-proof condition, add polypropylene wax powder to the reaction solution prepared in step S1-2, and disperse by ultrasonication to prepare a reaction dispersion; S1-4. The reaction dispersion prepared in step S1-3 is subjected to ultraviolet irradiation for more than 10 minutes under nitrogen protection, and the solid reaction product is filtered out, washed, and dried to obtain methyl methacrylate grafted polypropylene wax.

2. The low precipitation environmentally friendly WPC wood plastic floor lubricating material according to claim 1 is characterized in that: The mass proportions of the raw material components of the lubricating material include: 22-24 parts of methyl methacrylate grafted polypropylene wax, 36-38 parts of MBS resin powder, 10-12 parts of chlorinated paraffin, 18-20 parts of tricresyl phosphate, 6-8 parts of zinc borate, and 4-6 parts of silicone powder.

3. The low precipitation environmentally friendly WPC wood plastic floor lubricating material according to claim 1 is characterized in that: In the step S1-1, the concentration of benzophenone in the initiator solution is 40-60 g / L.

4. The low precipitation environmentally friendly WPC wood plastic floor lubricating material according to claim 1 is characterized in that: In the steps S1-2 and S1-3, the mass ratio of the added amount of methyl methacrylate and polypropylene wax powder is 0.7-1.4:

10.

5. The low precipitation environmentally friendly WPC wood plastic floor lubricating material according to claim 1 is characterized in that: In the step S1-4, the power of the ultraviolet light source for ultraviolet irradiation is not less than 1000W.

6. The low precipitation environmentally friendly WPC wood plastic floor lubricating material according to claim 1 is characterized in that: The particle size of the zinc borate is 100-325 meshes.

7. A method for preparing the low-precipitation environmentally friendly WPC wood plastic floor lubricating material according to claim 1, characterized in that: The following steps are involved: S1, preparing methyl methacrylate grafted polypropylene wax; S2, accurately weighing the formula amount of methyl methacrylate grafted polypropylene wax, chlorinated paraffin, tricresyl phosphate and zinc borate, and mixing them thoroughly to obtain a mixture a; S3, accurately weigh the MBS resin powder and silicone powder in the formula, mix them thoroughly, and obtain a mixture b; S4, adding the mixture a obtained in step S2 and the mixture b obtained in step S3 into a twin-screw extruder, and obtaining a low-precipitation environmentally friendly WPC wood-plastic floor lubricating material through extrusion and granulation.

8. The method for preparing the low-precipitation environmentally friendly WPC wood plastic floor lubricating material according to claim 7, characterized in that: In step S4, the temperature of each section of the twin-screw extruder is controlled within 165°C.

Citation Information

Patent Citations

  • PVC composite floor and preparation process thereof

    CN110294904A

  • Precipitation-free lubricant and preparation method thereof

    CN110628229A

  • Wood-plastic composite floor and manufacturing method thereof

    CN104631758A

  • Preparing process of solid phase grafted polyolefin wax copolymer

    CN1986588A

Cited By

  • Precipitation-free lubricant and preparation method thereof

    CN120365488A